PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN (Studi Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2010-2012) - Addiyah, Alina; Chariri, Anis (Diponegoro Journal of Accounting, 2014)
This study aims to examine the effects of corporate governance mechanism on the financial performance of banking. Financial performance is calculated by using CFROA, meanwhile the corporate governance mechanismdetermined by variable board of commissioners, board of directors, and firm size. The sample in this study were banking companies listed in Indonesian Stock Exchage (IDX) in a periode 2010-2012. The number of sample used were 23 companies listed were taken by purposive sampling. The method of analysis of this research used multi regression. The result of this research showed that board of commissioners had negative and significant influence to financial performance; board of directors had positive and significant influence to financial performance; and firm size had negative and significant influence financial performance.